(untitled) (diségno, 2024)
Between the Renaissance and the Age of Enlightenment, the theatrical spectacle moves from the static image, of the fixed scene, to the changing image of moving backdrops that simulate the centrality of frontally arranged spaces, evolving them into the Bibienesque corner view. The perspective’s theories and methods are progressively absorbed by empirical staging inventions, while drawings of individual apparatuses and machines that reveal their kinematics are often fragmentary. Even more so are the analog models, traces of which remain only in sporadic reconstructions displayed in exhibitions: they are magic boxes suitable for rediscovering the perspective space dimension, evoking the original mise-en-scène configurations. The essay rereads the maquettes by relating them to the iconographic and textual sources that determined their design logic. The burgeoning literature reflecting on the practices of theatricality from the second half of the sixteenth century onward is analyzed to rediscover the fundamentals of relief perspectives and the determination of the optimal point of view, starting with the constructive rules of the stage, evident as in the treatises of Scipione Chiaramonti and Nicola Sabbattini. This makes it possible to trace the real spatial configurations of the contexts in which the performances took place, while also verifying the proportionality relationships of the proscenium arch, which can be inferred from the study of the frontispieces and engravings accompanying the operas’ librettos.